Middle East politics for the new millennium a constructivist approach - Gordon, Louis A.; Oxnevad, Ian M. (Lexington Books, 2016)
This book explores the domestic and international relations of countries in the Middle East and North Africa using the focus of ideas and repeat interactions employed by constructivism of political trends and figures of the region to develop a deeper understanding of Middle East politics.